Land in Limbo: Understanding path dependencies at the intersection of the port and city of Naples - De Martino, Paolo (A+BE | Architecture and the Built Environment, 2021)
Numerous actors have been involved in the planning of the port and city of Naples. National and local authorities—namely central government, the Region, the Municipality of Naples, and the Port Authority—act upon the port at different scales, according to diverging interest and by using different planning tools. Each entity has different spatial claims and contrastive views on what port city integration can be. Their diverse goals have led port and city to develop into separate entities, from a spatial, cultural, economic as well as administrative perspective. The different scopes of their planning are particularly visible in the areas at the intersection of land and water, where the relationship is characterized by waiting conditions across different dimensions and scales. The separation between port and city in Naples originates from history. This PhD thesis looks at the past as a resource, sometimes as a problem in the way it produces inertia, but certainly as a heritage made of signs, traces, and cultures, written and rewritten on the urban palimpsest. Using and challenging the concept of path dependence—defined here as a resistance by institutions and people to change patterns of behavior and to repeat previous decisions and experiences—this PhD thesis argues that in order to overcome inertia, it is important to recognize the interests and spatial claims of all the stakeholders involved port city planning and to identify shared goals and values as a foundation for future design.